Analisis Korpus Bahasa Tentang Nilai Kepemimpinan KH Ahmad Dahlan Dalam Pidato Kepemimpinan Muhammadiyah Kontemporer - Primandhika, Restu Bias; Mulkhan, Abdul Munir; Sari, Zamah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to analyze the representation of KH Ahmad Dahlan's leadership values in contemporary Muhammadiyah speeches using corpus linguistic analysis. The data analyzed consisted of a corpus from KH Ahmad Dahlan's leadership texts and transcriptions of contemporary Muhammadiyah leaders' speeches. Corpus linguistic analysis was employed as the analytical method, supported by Python programming language on Google Colab utilizing several libraries such as the Natural Language Toolkit (nltk) and Sastrawi. The word frequency analysis revealed that in KH Ahmad Dahlan's text corpus, the words